201 Laparoscopic extra-peritoneal para-aortic node dissections in the belfast trust over the last 9 years: a single institution experience for locally advanced cervical carcinoma. (18th September 2019) - Reilly, K; Craig, E; Nagar, H; Dobbs, S; McComiskey, M; Harley, I
Abstract : Objectives: Cervical cancer is one of the most commonly occurring female cancers with increasing incidence. The mainstay of treatment for locally advanced disease is primary chemoradiotherapy. Pre-operative imaging in combination with laparoscopic extraperitoneal para-aortic node dissection (LEPAND) has been used to best target this treatment. This study looked at all women in the Belfast Trust over the last 9 years who had this investigation as part of their pre-treatment workup. Methods: Retrospective data was collected for all those who had LEPAND for locally advanced cervical cancer from January 2010 to December 2018. All women had pre-operative imaging that suggested positive pelvic nodes but negative para-aortic nodes. Results: Sixty women were identified in this group ageing 23–69 with median age 39. 93.3% had stage 2b cervical cancer, the remainder were 1b2 or 3b. 17% had adenocarcinoma of the cervix and 83% had squamous cell carcinoma. The median survival overall is 5 years. 70% of women had primary LEPAND surgery before chemoradiotherapy with the remainder having primary treatment before surgery. 15% of the study population died, 90% of which died within two years of diagnosis. 67% of these women had primary LEPAND followed by chemoradiotherapy with the others proceeding straight to primary treatment prior to surgery. 5% (3/60) had positive para-aortic nodes on histopathology although 100% appeared node negative on MRI/PET imaging. None with positive nodes had recurrences but 66% died within 2 years. Conclusions: Despite having negative nodes on imaging 5% had positive para-aortic lymph nodes on histopathology. LEPAND surgery prevented undertreatment in these women.